Smart congestion relief. Comprehensive evaluation of traffic congestion costs and congestion reduction strategies. - Litman, Todd (My University, 2014)
How traffic congestion is evaluated can significantly affect transport planning decisions. This report describes various factors that affect congestion cost estimates and the evaluation of potential congestion reduction strategies, including analysis scope, baseline speeds, travel time valuation, accident and emission impact analysis, induced travel analysis, and consideration of co-benefits. It discusses how these factors influence planning decisions, and describes best practices recommended by experts. It applies these methods to evaluate various congestion reduction strategies including roadway expansion, alternative mode improvements, pricing reforms, smart growth policies and demand management programs.
Keywords: Individualverkehr; Fahrradverkehr; Stadtverkehr; Verkehrsbelastung; Autoverkehr; Kostenanalyse; Verkehrskosten; Evaluation; Multimodalität